Efeitos do treinamento intervalado de alta intensidade e dos seus diferentes protocolos sobre o perfil lipídico e o controle glicêmico em indivíduos com diabetes tipo 2: uma revisão sistemática - Cavalli, Nandiny Paula (2022)
Glycemic and lipid control are essential for preventing long-term complications and reducing mortality in type 2 diabetes mellitus (T2DM). High-intensity interval training (HIIT) is an alternative to moderate-intensity continuous training (MICT) in T2DM individuals and is able to promote benefits in terms of metabolic health. Different HIIT protocols have been used in studies evaluating different outcomes, however its effects on glycemic control need more evidence and its influence on lipid profile are still uncertain in T2DM individuals. The aim of this study was to systematically review the effects of HIIT and its different protocols, in comparison to MICT or control, on lipid profile and glycemic control variables in individuals with T2DM. Search strategy was performed in the PubMed/MEDLINE, Cochrane CENTRAL, Web of Science, Sport Discus, Embase and PEDro databases, using the descriptors “Diabetes Mellitus, Type 2” and “High-Intensity Interval Training”. Randomized clinical trials which evaluated the effects of HIIT on T2DM individuals on total cholesterol, HDL, LDL, triglycerides, HbA1c and fasting glucose were included. Study selection by title, abstract and full text, as well as data extraction and risk of bias assessment was performed by two independent reviewers. The meta-analysis was performed using a Random effects model, and data were presented as mean difference and 95% confidence interval. Risk of bias was assessed using the RoB 2.0 tool, and certainty of evidence according to the GRADE system. In comparison with control, HIIT promoted a reduction in total cholesterol of -0.31 mmol/L (95% CI -0.49; -0.12; I2 = 0%), in LDL of -0.31 mmol/L (95% CI -0.49; -0.12; I2 = 47%), and in triglycerides of -0.27 mmol/L (95% CI -0.33; -0.2; I2 = 0%), as well as an increase in HDL levels of 0.24 mmol/L (95% CI 0.06; 0.42; I2 = 96%). Stil in the comparison between HIIT and control, HIIT promoted a reduction in HbA1c of -0.75% (95% CI -0.97; -0.53; I2 = 73%) and in fasting glucose of -1.15 mmol/L (95% CI -1.44; -0.86; I2 = 0%). In the comparison between HIIT and MICT, no difference was found for any of the outcomes analyzed, however subgroup analysis showed a reduction in total cholesterol levels with a moderate-interval and moderate-term protocol, and also a reduction in LDL levels with MICT when compared to a short-interval HIIT protocol.